Prenatal stress induces learning deficits and is associated with a decrease in granules and CA3 cell dendritic tree size in rat hippocampus - HOSSEINI-SHARIFABAD Mohammad; HADINEDOUSHAN Hossein (Anatomical science international, 2007)
Exposure to gestational stress impairs hippocampal‐dependent learning in offspring. In spite of the known decisive role of hippocampal dendritic architecture in learning and memory, there has been no study to date that examines the effect of prenatal stress on the morphology of the hippocampal neurons. Therefore we performed a quantitative morphological analysis of the dendritic architecture of Golgi‐impregnated hippocampal neurons in prenatally stressed rats. Subjects included male rat offspring (2 months old) for which the mothers had been restrained for 1 h/day during the last week of gestation. Spatial learning performance levels using Morris water maze and changes in the morphology of hippocampal dendritic trees were studied. Results indicated that the study group had lower spatial learning capabilities along with decreased length and number of dendritic segments, branching of granules and cornu ammonis (CA)3 pyramidal cells. There was no change in the dendritic morphology of CA1 pyramidal cells. These results suggest that prenatal stress in rat results in spatial learning deficits and profound alterations in the neurites of the hippocampal cells of male offspring.